A HYBRID FOURIER TRANSFORM -EMPIRICAL MODE DECOMPOSITION MODEL FOR LEAKAGE DETECTION - MOHD JAAFAR, NUR SYAKIRAH (2019)
The development of underground pipeline plays a vital role in the advancement of the oil and gas industry in Malaysia and worldwide. Most existing pipelines are aged and tend to fail due to external and internal factors. Material fatigue, sudden changes in pipeline pressure or other critical factors lead to failure in pipelines and their material properties, impact on environmental conditions, and excessive internal and external loads. When the pipeline starts to deteriorate through mechanisms such as leakage, it is regarded as experiencing failure. Due to the rapid increase of spending on pipeline leak detection for the oil and gas industry, it is a challenging task to study the ways in which information from the time–frequency analysis of signal processing is communicated about leakages in pipelines.